Phone triage nurses' assessment of respiratory tract infections - the tightrope walk between gatekeeping and service providing. A qualitative study - Bent Håkan Lindberg; Ingrid Keilegavlen Rebnord; Sigurd Høye (Taylor & Francis Group, 2021)
Background Phone nurses triage callers to Norwegian out-of-hours cooperatives to estimate the appropriate urgency and level of care for the caller. Many callers with mild symptoms of respiratory tract infections receive a doctor's consultation, which may lead to busy sessions and in turn impair clinical decisions. Objective This study explores how phone triage nurses assess callers with mild-to-moderate symptoms of respiratory tract infections and their views and experiences on triaging and counselling these callers. Methods We conducted four focus groups with 22 nurses (five men and 17 women aged 24-66 years) in three different locations in Norway. The interviews were transcribed verbatim and analysed by systematic text condensation. Results The informants were reluctant to call themselves gatekeepers. However, their description of their work indicates that they practice such a role. When nurses and callers disagreed about the right level of care, the informants sought consensus through strategies and negotiations. The informants described external factors such as organisational or financial issues as decisive for the population's use of out-of-hours services. They also described callers' characteristics, such as language deficiency and poor ability to describe symptoms, as determining their own clinical assessments. Conclusions Nurses perceive assessments of callers with respiratory tract infections as challenging. They need skills and time to reach a consensus with the callers and guide them to the right level of health care. This should be considered when planning nurse training and staffing of out-of-hours cooperatives.KEY-POINTS Phone triage nurses assess callers to the out-of-hours service and estimate the level of urgency This study explores how phone triage nurses assess callers with respiratory tract infections and their views and experiences on this task The nurses describe their professional role as a tightrope walk between gatekeeping and service providing The nurses seek consensus with callers through strategies and negotiations